PENERAPAN KURIKULUM PESANTREN DAN KEMENAG MEMBENTUK KARAKTER SANTRI RAHMATAN LIL ALAMIN DI MTS SAINS SALAHUDDIN WAHID - Purwo Hadi Saputro; Sholihul Anshori (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Curriculum development is the most important part in improving the quality of learning. Curriculum development is very important to increase the success of the education system as a whole because the curriculum is a factor in improving the quality of education. Along with developments in science and technology, the government always makes various improvements and efforts to improve the curriculum or materials in education programs.The problem discussed in this research is whether it is appropriate to implement the Islamic Boarding School Curriculum and the Ministry of Religion to Shape the Character of Santri Rahmatan Lil Alamin At MTs Science Salahuddin Wahid. Based on the problems above, this research aims to describe the process of implementing the Islamic Boarding School Curriculum and the Ministry of Religion to Shape the Character of Santri Rahmatan Lil Alamin At MTs Science Salahuddin Wahid.The type of research is case study research. The research was carried out using a qualitative approach with descriptive methods. Data collection was carried out using interviews, observation techniques and documentation studies. The informants in this research consisted of the Principal, Deputy Head of Curriculum, Deputy Head of Student Affairs, Counseling Guidance Teacher, and Students. Data collected for observations and interviews were analyzed using data source triangulation analysis techniques.Based on the research results, it was found that: The head of the Madrasah at MTS Sains had implemented the Islamic boarding school and Ministry of Religion curriculum. The Head of Mts Science Curriculum, with the help of the Head of Student Affairs and Counseling Guidance Teachers, implemented the Implementation of the Islamic Boarding School Curriculum and the Ministry of Religion, Shaping the Character of Santri Rahmatan Lil Alamin At MTs Science Salahuddin Wahid, making it easier for students to build the character of Santri Rahmatan Lil Alamin. Thus producing students who are competent and have the character of Rahamatan lil alamin.